COPD awareness in the urban slums and rural areas around Pune city in India - Deesha Deepak Ghorpade (Nature Portfolio, 2021)
Abstract COPD is the second leading cause of death and disability adjusted life years (DALYs) in India, yet, it remains poorly recognized. We aimed to study the level of awareness of COPD in urban slums of Pune city in India and its neighboring rural areas. All male and female subjects above the age of 30 years residing in 13 randomly selected slums of Pune city (total population of 3000) and 7 randomly selected neighboring rural villages (total population of 3000) were invited to participate in this cross-sectional community survey. After obtaining written informed consent, 13 trained community health workers (CHWs) administered a questionnaire that captured their level of awareness of COPD. Of the 6000 subjects approached, 5420 residents (mean age ± SD = 48.0 ± 13.5 years; 38% males) consented and answered all questions. The number of people who had ever heard the word COPD was 49/5420 [0.9% (0.6–1.1%); 0.7% (0.5–1.3%) of the urban slum dwellers and 1.15% (0.5–1.3%) of rural residents]. Among those who had never heard the word COPD (n = 5371), when asked what was the name of the disease caused by long-term tobacco smoking, 38% said cancer, 16.7% said asthma, and 4.4% said TB. Among those who had heard the word COPD (n = 49), 6.1% said it was a disease of the heart, and 61% attributed COPD to smoke and dust pollution and 20% to tobacco smoking. The level of awareness of COPD in the Indian community is extremely low, highlighting the need to have nationwide mass awareness programs in India.